Wavelength dependent transmission in multimode graded-index microstructured polymer optical fibers - Simović, Ana; Savović, Svetislav; Wang, Zhuo; Drljača, Branko; Kovačević, Milan S.; Kuzmanović, Ljubica; Djordjevich, Alexandar; Aidinis, Konstantinos; Chen, Chen (Frontiers in Physics, 2024)
Up to now, there were no commercial simulation tools accessible for researching the transmission properties of multimode microstructured optical fibers (MOFs). In order to avoid this problem, this study uses the time-independent power flow equation (TI PFE) numerical solution to examine the wavelength dependency of the equilibrium mode distribution (EMD) and steady state distribution (SSD) in multimode graded-index microstructured polymer optical fiber (GI mPOF) with a solid core. We showed that the lengths zs at which an SSD is obtained in GI mPOF and the coupling length Lc necessary to create an EMD are shorter at λ=568 nm than they were found to be at λ=633 nm. The lengths Lc and zs stay constant when the wavelength decreases further from λ=568 to 522 and then to 476 nm. As a result, it is anticipated that a faster bandwidth enhancement in the tested GI mPOF will take place at wavelengths around λ=568 nm as opposed to λ=633 nm. Such a bandwidth improvement is not brought about by additional wavelength reduction. The study's findings can be used in communication and sensory systems that use multimode GI mPOFs at different wavelengths.